Regesten zur Geschichte der Juden in Österreich im Mittelalter, Band 2 Band 2: 1339-1365 - Brugger, Eveline (Studien Verlag, 2010)
A remarkably high number of medieval sources on the history of Jews can be found in Austria. This huge amount of sources provides information on the economic, legal and personal situation of the Jews as well as on the interactions between Christians and Jews. Therefore, the Institute for Jewish History in Austria has engaged in preparatory work to publish this source material. In the course of the FWF project P 15638, the first volume of these sources (from the beginnings until 1338) was published by Eveline Brugger and Birgit Wiedl, and research for the second volume was begun. In the course of the follow-up project "Documents on Jewish History in Austria 1339-1365", this research was completed and the volume prepared for publication. Charters as well as historiographic and literary sources containing references to both Jews and Austria were collected and processed according to scientific criteria. This material includes a considerable number of texts which have not been published at all or treated with regard to the Jewish aspect yet. Research was carried out in archives both in Austria and abroad; furthermore, previously published material was also collected. The resulting manuscript consists of a chronological series of 682 document summaries. The apparatus includes information about the form the text was preserved in (original, copies), former publications in printing (full text or summaries) or online as well as the literature that is relevant to the respective document. Additionally, an extensive index as well as a scientific commentary were added to the relevant document to make the source texts accessible to the reader. Given the volume's topic, the Jews mentioned in the source text were the main focus of these commentaries. The sources which were collected and processed in preparation of the second volume cover a critical period of time for the Austrian Jews. It is of crucial importance that any comprehensive study of this period is based on the entirety of the source material, which is now readily available in the finished volume. Both the consequences of the Pulkau persecution of 1338, which wiped out a number of smaller Jewish settlements, and the impact which the plague had on the Austrian Jews are reflected in these sources. Besides, these sources allow a more detailed analysis of the policies which the dukes Albrecht II and Rudolf IV pursued towards the Jews, which in turn provides insights into the legal, social and economic situation of the Austrian Jews during this period.